ANTI-MILITARY CONCEPTOSPHERE IN UKRAINIAN PROSE ABOUT THE EVENTS OF THE FIRST WORLD WAR - Tovt, Olha (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
The purpose of the article: to investigate the anti-military conceptual sphere in Ukrainian prose about the events of the First World War, identifying the dominant concepts in it. The subject of study is the concepts of "memory" and "war". The object of scientific understanding is the prose works of Osyp Turianskyi, Stepan Vasylchenko, Osyp Makovei, Marko Cheremshyna, Vasyl Stefanyk, Natalia Kobrynska, Olha Kobylianska, Timotei Bordulyak, Yura Shkrumelyak, Mykhailo Yatskiv, Mykola Matiiev-Melnyk, Oleksa Kobets, Mykhailo Lomatskyi and Volodymyr Lopushanskyi. Such a choice for the analysis of the works is arbitrary, partly due to the presence of their texts in the currently only anthology of such prose "...Because war is war..." and the expressiveness of their anti-military conceptual sphere. The scientific methodology consists in the fact that the article uses philological, hermeneutic and biographical methods, as well as methods of linguistic and literary analysis. The novelty of the study is already in its name, and its results are in the analysis of the dominant concepts that create the original anti-military conceptosphere with the hyperconcepts of "memory" and "war". It is proved that the concept of "memory" in the prose of Ukrainian authors is multifaceted (at the level of the individual, collective, autobiography, associative), and the concept of "war" appears in Ukrainian writing as an integral component of the general picture of the world and in the analyzed works outlines its specificity of ideological and aesthetic embodiment. The practical value of the article carries a specific direction: its results can be used in the study of the work of individual Ukrainian artists of the word, as well as in the historical-literary review of national writing.